Variasi temporal dan spasialtinggi muka air tanah gambut lokasi demplot ICCTF jabiren kalimantan tengah - Hendri Sosiawan; Budi Kartiwa; Wahyu Tri Nugroho; Haris Syahbuddin (Universitas Pembangunan Nasional Veteran Yogyakarta, 2017)
As the swamp ecosystem, the presence of water in the peat is strongly influenced by the characteristic of rain and river tide. Thus the role of rivers and canals in cultivated peatlands is especially important to maintain the optimal water level fluctuations for crops. Demplot ICCTF in Jabiren, Pulang Pisau District, Central Kalimantan peat land was cultivated for rubber plant community,located beetwen the river Jabiren (secondary canal) and tertiary canal. The objective is to determine the peatland water level fluctuations both temporally and spatially. To achieve this objective, these activities have been implemented i.e: topographic survey, installation of piezometer and staff gauge, and water level observation. Topographic survey has been carried out to map land elevation, position and elevation of water level observation device and water infrastucture. Observation of the spatial dynamics of ground water level was done manually, and the temporal dynamic of water level in canal inlet and outlet observed automatically using loggers. Results shows that the groundwater level fluctuations have a simillar tendency with water level of the river and tertiary canal. Spatial variation of groundwater level elevation shows that the highest groundwater level was the farthermost of piezometer from the canal or river. Hydrotopograpy land shows that the pattern of ground water level pattern like a dome. This indicates that the peatland of Jabiren ICCTF research demonstration plot that began to be cultivated for rubber plant in 2006 has not experienced subsidence significantly. Result indicates also that temporal fluctuation of ground water level was strongly influenced by pattern fluctuation of water level ofsecondary canal inlet but it was not influenced by secondary canal outlet. The tertiary canals flapegates must be funtioned well in order to maintain the optimal depth of groundwater as water level does not fluctuate. The secondary channel as serves as a transport services must be temporary installed by flapegate at downstream so that the duration of the water level in the channel will last longer and ultimately affect positive on the water level in the cultivated land.